21. STUDY ABDOMINAL AORTA ANATOMY USING MULTI-SLICE COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the anatomical variation and the sizes of the abdominal aorta of some Vietnamese adults using 64-slices computed tomography. Subjects and methods: A cross-sectional study was conducted in 64-slices computed tomography results with volume rendering of 24 patients at Tâm Anh General Hospital, Hanoi, from 2022 to 2023. Results: The abdominal aorta began at aortic hiatus. It was located at the levels of T12, T12-L1 intervertebral disc, T11-T12 intervertebral disc, and L1 in 17, 5, 1, and 1 cases, respectively. The abdominal aorta terminated in a bifurcation into the common iliac arteries at L4 and L4-L5 intervertebral disc levels in 19 and 5 cases, respectively. The mean length of the abdominal aorta was 127.16mm. The mean diameters of the abdominal aorta at the origin, above the levels of renal arteries origin, and the termination were 21.64, 18.26, and 15.25mm, respectively. Conclusion: The origin and termination of the abdominal aorta varied in vertebral levels. The abdominal aorta’s size was considerable. Its length was greater in males compared to females. Its diameter was reduced from origin to termination.
Keywords: Abdominal aorta, length, diameter.